MIGRATION SUBJECT-MATTER IN THE INTERDISCIPLINARY SPACE OF ETHNOSOCIOLOGY - M. P. Zamotin (Дискурс, 2017)
Migration studies and questions from an importance position for ethnosociological space of studying of migration problems in Russia and the related problems of ethnosociology as identity, ethnicity, conflict, and ethnic structure are considered. The attention is paid to a problem of ethnicity and approaches to its interpretation. Special attention is paid to the aspect of ethnic migration as a phenomenon as well as from the point of view of approaches. A number of problem areas in the study of ethnic migration such as: a generational problem, adaptation strategies in the urban environment (based on the examples of particular research), political measurement of migration, discriminatory social practices, formation of social networks of migrant communities are considered in the article.